A characterization of HULIS-C and the oxidative potential of HULIS and HULIS-Fe(II) mixture in PM2.5 during hazy and non-hazy days in Shanghai. (15th December 2019) - Lu, Senlin; Win, Myat Sandar; Zeng, Junyang; Yao, Chuanhe; Zhao, Mengfei; Xiu, Guangli; Lin, Yichun; Xie, Tingting; Dai, Yafeng; Rao, Lanfang; Zhang, Luying; Yonemochi, Shinich; et al.
Abstract: Humic-like substances (HULIS) were isolated from PM2.5 in Shanghai. The oxidative potential and the cytotoxicity of the isolated HULIS and its Fe(II) binary mixtures were evaluated by using cell-free Dithiothreitol (DTT) and cellular 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assays. Our data showed that HULIS-C contents in spring during hazy and non-hazy days were relatively higher than in winter. Cell-free DTT and bioassay (reactive oxygen species (ROS) and MTT) results showed that higher ROS values were released from individual HULIS or SRFA (Suwannee River Fulvic Acid) compounds than HULIS-Fe(II) complexes and Fe(II) alone. In addition, DTT and ROS correlation results were in line with each other and the oxidative potentials of HULIS and its binary mixtures were strongly inter-correlated with carbonaceous components (WSOC, OC) in PM2.5 . Dose-dependent MTT results revealed that cell mortality positively correlated with the mass concentrations of HULIS (10–50 μg/ml). In the HULIS-Fe(II) system, the ROS generation ability depended on the mixing time of HULIS-C with Fe(II), thus suggesting that the organic-metal complexation time and the Fenton reaction induced by Fe (II) play a role in the cell mortality rate. Graphical abstract: Image 1 Highlights: Higher reactive oxygen species from HULIS-Fe(II) complexation than Fe (II) alone. Reactive oxygen species generation depending on the mixing time with Fe(II). Oxidative potentials of HULIS and its binary mixtures strongly inter-correlated with WSOC/ OC.